Allegory, portrait, manifesto? A review of interpretations of Artemisia Gentileschi’s “La Pittura” - Huanca Lara, Grecia (2025)
The article examines the main interpretive trends that have emerged around Artemisia Gentileschi’s La Pittura. It argues that interpretations of this painting have been shaped by two main approaches: one that highlights the artist’s exceptionality and agency, and another that proposes a critical decentralization of that very exceptionality. Through the analysis of these perspectives, the study contends that the painting has become a fertile ground for debate on self-representation, gender, and female agency in Baroque art.